Occurrence and diversity pattern of CRISPR-Cas systems in Acetobacter genus provides insights on adaptive defense mechanisms against to invasive DNAs - Ghaffarian, Sara; Panahi, Bahman (Frontiers in Microbiology, 2024)
The Acetobacter genus is primarily known for its significance in acetic acid production and its application in various industrial processes. This study aimed to shed light on the prevalence, diversity, and functional implications of CRISPR-Cas systems in the Acetobacter genus using a genome mining approach. The investigation analyzed the CRISPR-Cas architectures and components of 34 Acetobacter species, as well as the evolutionary strategies employed by these bacteria in response to phage invasion and foreign DNA. Furthermore, phylogenetic analysis based on CAS1 protein sequences was performed to gain insights into the evolutionary relationships among Acetobacter strains, with an emphasis on the potential of this protein for genotyping purposes. The results showed that 15 species had orphan, while20 species had complete CRISPR-Cas systems, resulting in an occurrence rate of 38% for complete systems in Acetobacter strains. The predicted complete CRISPR-Cas systems were categorized into I-C, I-F, I-E, and II-C subtypes, with subtype I-E being the most prevalent in Acetobacter. Additionally, spacer homology analysis revealed against such the dynamic interaction between Acetobacter strains and foreign invasive DNAs, emphasizing the pivotal role of CRISPR-Cas systems in defending against such invasions. Furthermore, the investigation of the secondary structures of CRISPR arrays revealed the conserved patterns within subtypes despite variations in repeat sequences. The exploration of protospacer adjacent motifs (PAMs) identified distinct recognition motifs in the flanking regions of protospacers. In conclusion, this research not only contributes to the growing body of knowledge on CRISPR-Cas systems but also establishes a foundation for future studies on the adaptive defense mechanisms of Acetobacter. The findings provide valuable insights into the intricate interplay between bacteria and phages, with implications for industrial applications and potential biotechnological advancements.